Medicine meets virtual reality 19: NextMed - Westwood, James D.; Westwood, Susan W. (Studies in health technology and informatics, 2012)
Title Page; Preface; MMVR19 Proceedings Editors; MMVR19 Organizing Committee; Contents; A Meshless EFG-Based Algorithm for 3D Deformable Modeling of Soft Tissue in Real-Time; Design of a 4 DOF Laparoscopic Surgery Robot for Manipulation of Large Organs; Virtual Help for Real Surgery: The Case of Awake Surgery; Enhancing Medical Communication Training Using Motion Capture, Perspective Taking and Virtual Reality; Medical Students' Attitudes Toward Obese Patient Avatars of Different Skin Color; Abnormal Red Blood Cells Detection Using Adaptive Neuro-Fuzzy System
Includes bibliographical references and indexes. - Description based on print version record
Keywords: Electronic books; Congress; Konferenzschrift -- 19